Expanded perlite material with shell / core composite structure and preparation method of expanded perlite material

By coating the surface of perlite ore particles with a glassy, ​​porcelain, or ceramic shell, a closed-cell shell/core composite expanded perlite material is formed. This solves the problem of gas escaping and forming open cavities during the expansion process of traditional expanded perlite materials, improves mechanical strength and thermal insulation performance, and broadens the application range.

CN120887739APending Publication Date: 2025-11-04SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510969125.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Traditional expanded perlite materials release gas during the expansion process, creating open cavities that reduce their lightweight and thermal insulation properties. Furthermore, their bonding strength with cementing materials is insufficient, limiting their application range.

Method used

The shell/core composite structure is adopted, which forms a closed-cell structure by coating the surface of perlite ore particles with a glassy, ​​porcelain and ceramic outer shell, thereby improving mechanical strength and thermal insulation performance.

Benefits of technology

It achieves high expansion ratio, low water absorption, low thermal conductivity and high mechanical strength, enhances lightweight, thermal insulation and sound insulation performance, and broadens the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120887739A_ABST
    Figure CN120887739A_ABST
Patent Text Reader

Abstract

The invention provides a shell / core composite structure expanded perlite material and a preparation method thereof.The shell / core composite structure expanded perlite material comprises an outer shell and an inner core, the outer shell sequentially comprises a vitreous layer, a ceramic layer and a ceramic layer from inside to outside or sequentially comprises a vitreous layer, a ceramic layer and a ceramic layer from inside to outside, and the inner core comprises an outer shell and an inner core. The inner core is an expanded product of perlite ore particles. The preparation method comprises the following steps: pretreating perlite ore particles, and mixing the pretreated perlite ore particles with a binder to obtain first perlite particles; adding the vitreous cladding powder into the first perlite particles for granulation, then adding one of the porcelain cladding powder and the ceramic cladding powder for granulation, and then adding the other one for granulation; obtaining second perlite particles; drying and preheating the second perlite particles to obtain third perlite particles; and performing high-temperature expansion on the third perlite particles to obtain the expanded perlite material with the shell / core composite structure. The closed-cell expanded perlite obtained by the invention has higher expansion time and lower water absorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mineral and rock material processing and new material technology, specifically to a shell / core composite structure expanded perlite material and its preparation method. Background Technology

[0002] Perlite minerals, including perlite type, obsidian type, and resinstone type, are acidic silicate glasses formed by the rapid cooling of acidic volcanic lava. Due to the rapid cooling rate, the water in the lava is uniformly sealed in the glass.

[0003] Under suitable high-temperature conditions (generally 1000–1300℃), perlite ore particles can rapidly expand several times their original size, forming lightweight, porous expanded perlite with properties such as thermal insulation, sound insulation, and fire resistance. This is because the acidic silicate glass melts during high-temperature firing, and the water within it expands as gas within the molten glass. Expanded perlite demonstrates broad application potential in multiple fields, especially as a raw material for the production of lightweight and insulating materials, occupying an important position in the construction and manufacturing industries.

[0004] However, expanded perlite produced by traditional methods suffers from drawbacks such as open cavities left by gas escape during the expansion process, irregular shape, low strength, and hygroscopicity. These problems lead to a decline in product performance during composite material preparation and use. For example, open cavities can easily lead to the infiltration of cementitious / bonding material slurry, reducing lightweight and thermal insulation properties, thus limiting its application range. To overcome these defects, researchers have tried various improvement methods, including organic modification and surface coating techniques. However, these methods often introduce new problems, such as affecting the bonding strength of the substrate.

[0005] In recent years, with technological advancements, breakthroughs have been achieved in producing closed-cell expanded perlite using an electric expansion furnace under precise temperature control, addressing the porous structure of expanded perlite. This method, through precise temperature control, melts the glassy layer on the surface of expanded perlite particles, causing the surface to collapse and form closed-cell expanded perlite, sealing the open pores. This significantly improves the material's strength and water resistance while maintaining good thermal and sound insulation properties. However, this method is limited by the precise control of the furnace temperature, and the surface collapse of the expanded perlite particles affects the bulk density, thermal conductivity, and final product performance of the expanded perlite.

[0006] Therefore, exploring a new production method of closed-cell expanded perlite, overcoming the defects of the expanded perlite produced by the traditional method, such as the open holes on the surface of the expanded perlite, easy to cause the decrease of the light weight and thermal insulation performance of the expanded perlite after the slurry of cementing / cementing material is poured in, is an urgent technical problem to be solved at present, and the present application has great significance. SUMMARY

[0007] In view of the problems in the prior art, the present application aims at solving one or more of the above problems in the prior art. For example, one of the purposes of the present application is to provide a shell / core composite structure expanded perlite material which is closed-cell, has higher expansion ratio, mechanical strength and sound absorption rate, lower water absorption rate, slurry absorption rate and thermal conductivity than ordinary expanded perlite. For another example, another purpose of the present application is to provide a preparation method of the shell / core composite structure expanded perlite material which can make full use of the perlite ore particles and effectively seal the internal holes.

[0008] In order to achieve the above-mentioned purposes, in one aspect of the present application, a shell / core composite structure expanded perlite material is provided, which can include an outer shell and an inner core, wherein the outer shell sequentially includes a vitreous layer, a porcelain layer and a ceramic layer from inside to outside, and the inner core is an expanded product of perlite ore particles.

[0009] According to one exemplary embodiment of one aspect of the present application, the total thickness of the outer shell can be 0.15-1mm, wherein the thickness of the vitreous layer, the porcelain layer and the ceramic layer is 0.05-0.5mm; and the diameter of the inner core ranges from 2 to 28mm.

[0010] Another aspect of the present application provides a preparation method of the shell / core composite structure expanded perlite material as described above, which can include: mixing the perlite ore particles after pretreatment and processing with a binder to obtain first perlite particles; adding the vitreous coating powder to the first perlite particles for granulation first, then adding the porcelain coating powder for granulation after completion, and then adding the ceramic coating powder for granulation after completion; or, adding the vitreous coating powder to the first perlite particles for granulation first, then adding the ceramic coating powder for granulation after completion, and then adding the porcelain coating powder for granulation after completion; obtaining second perlite particles; drying and preheating the second perlite particles to obtain third perlite particles; and performing high-temperature expansion treatment on the third perlite particles to obtain the shell / core composite structure expanded perlite material.

[0011] According to one exemplary embodiment of another aspect of the present application, the perlite ore particles can include one or more of perlite type, obsidian type, pitchstone type and pumice-like perlite.

[0012] According to an exemplary embodiment of another aspect of the present application, the first perlite particles can be obtained by mixing the pre-processed perlite particles having a particle size range of +100 to -10 mesh with the binder in a mass ratio of 100:(3-9).

[0013] According to an exemplary embodiment of another aspect of the present application, the binder can include an aqueous solution or hydrogel configured with industrial water and an inorganic binder and / or an organic binder; wherein the inorganic binder can include one or more of water glass having a modulus of 1.0-2.9, sodium silicate, and potassium silicate, and the inorganic binder is configured to have an aqueous solution having a density of 1.36-1.50 g / cm 3 38.4-48.3; the organic binder can include one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, acrylic emulsion, vinyl acetate emulsion, polyvinyl acetal glue, emulsion glue, animal glue, and vegetable glue, and the organic binder is configured to have a hydrogel having a solid content of 0.5-2.0% by mass; and the inorganic binder and the organic binder are mixed to form the binder, and the volume ratio of the inorganic binder to the organic binder can be 5:1-2:1.

[0014] According to an exemplary embodiment of another aspect of the present application, the first perlite particles, the vitreous shell powder, the porcelain shell powder, and the ceramic shell powder can be granulated in a mass ratio of (90-75):(10-20):(1-15):(1-15).

[0015] According to an exemplary embodiment of another aspect of the present application, the vitreous shell powder can be formed by mixing the pre-processed perlite micropowder having a particle size of less than 100 mesh, albite, borax, and boric acid in a mass ratio of (50-70):(20-35):(2-10):(0-10); the vitreous shell powder can have a particle size of -200 to -600 mesh; the porcelain shell powder can be formed by mixing the pre-processed perlite micropowder having a particle size of less than 100 mesh, albite / potassium feldspar, kaolin, and quartz sand in a mass ratio of (10-30):(20-40):(20-30):(10-20); the porcelain shell powder can have a particle size of -200 to -600 mesh; and the ceramic shell powder can be formed by mixing fireclay, shale, potassium feldspar, and quartzite in a mass ratio of (30-60):(20-40):(10-25):(5-15); the ceramic shell powder can have a particle size of -200 to -600 mesh.

[0016] According to an exemplary embodiment of another aspect of the present application, the drying can include drying the second perlite particles by raising the temperature from room temperature to 200-300°C at a temperature raising rate of 8-20°C / min; the pre-heating can include pre-heating the second perlite particles at a temperature of 500-850°C; and the third perlite particles can have a moisture content of 2-3%.

[0017] According to an exemplary embodiment of another aspect of the present application, the high-temperature expansion process can include sharply heating and rapidly expanding the third perlite particles by allowing the third perlite particles to stay in a high-temperature environment of 1100-1350°C for 2-80s.

[0018] Compared with the prior art, the present application has the following beneficial effects at least one of which is included:

[0019] (1) The shell / core composite structure expanded perlite material has an inner core of expanded perlite and a closed hard shell, and has excellent properties such as high expansion ratio and mechanical strength, low bulk density and thermal conductivity, low water absorption, and acid and alkali resistance, and further has better lightweight, thermal insulation, sound insulation, and other process properties.

[0020] (2) The shell / core composite structure expanded perlite material is subjected to coating and granulation treatment, has high sphericity, and the shell is a hard material composed of glass and porcelain and ceramic materials with higher strength, and has excellent properties such as lightweight, thermal insulation, sound insulation, and other properties of traditional expanded perlite, and can be used instead of ceramic particles, floating beads, and glass beads.

[0021] (3) The shell / core composite structure expanded perlite material also has particularly excellent mechanical strength, high surface hardness, and good bonding properties with organic binders or inorganic cementitious material matrices; during production, transportation, composite material and product preparation, and use, almost no dust is generated, and the production, transportation, and storage environment is not polluted. BRIEF DESCRIPTION OF DRAWINGS

[0022] The above and other objects and features of the present application will become more apparent from the following description made with reference to the accompanying drawings, in which:

[0023] Figure 1 A preparation process flow diagram of the shell / core composite structure expanded perlite is shown;

[0024] Figure 2A A photograph of ordinary expanded perlite is shown;

[0025] Figure 2B A photograph of the shell / core composite structure expanded perlite is shown;

[0026] Figure 3A A photograph of ordinary expanded perlite is shown;

[0027] Figure 3B An optical microscope photograph of the shell / core composite expanded perlite is shown;

[0028] Figure 4A An electron microscope photograph of the ordinary expanded perlite is shown;

[0029] Figure 4B An electron microscope photograph of the shell / core composite expanded perlite is shown;

[0030] Figure 5A An SEM image of the shell / core composite expanded perlite sample is shown;

[0031] Figure 5B Another SEM image of the shell / core composite expanded perlite sample is shown. DETAILED DESCRIPTION

[0032] Hereinafter, a shell / core composite expanded perlite material and a method of manufacturing the same will be described in detail in conjunction with the accompanying drawings and exemplary embodiments.

[0033] In the description of the present application, it is to be understood that the terms "first", "second", "third", etc. are merely intended for convenience and clearness in describing the application and are not construed to refer to or imply relative importance or a specific number of technical features indicated. Thus, the features defined with "first", "second", "third", etc. can explicitly or implicitly include one or more of the features. In the description of the present application, the meaning of "a plurality of", "several" is two or more, unless otherwise specified. The granularity expression existing in the present application, such as +100~ -10 mesh, expresses the meaning that the particles are above 100 mesh sieve and below 10 mesh sieve, the particles cannot pass through the 100 mesh mesh but can pass through the 10 mesh mesh; that is, the negative number indicates that the particle size is smaller than the mesh size; the positive number indicates that the particle size is larger than the mesh size.

[0034] The present application can coat the surface of perlite ore particles with heterogeneous materials that can form vitreous, porcelain and ceramic shells by a surface coating method. When the coated perlite ore particles are expanded, the coated vitreous heterogeneous materials first melt and trap the gas released during the expansion of the perlite ore particles, not only forming a vitreous shell layer on the surface of the expanded perlite and forming closed-cell expanded perlite, but also further improving the expansion ratio, sphericity and overall performance. The coated porcelain / ceramic heterogeneous materials form a porcelain / ceramic shell layer on the surface of the expanded perlite, which is beneficial to the formation of high-strength bonding with cementitious materials. This new type of shell / core structure expanded perlite material has excellent properties such as low bulk density, low thermal conductivity, high sphericity and high strength. In particular, during the molding process of lightweight, thermal insulation materials, the closed-cell structure of the expanded perlite not only prevents the cementitious / cementitious material slurry from being filled, but also the high sphericity can form a higher tight packing to reduce the use of cementitious / cementitious materials. At the same time, the porcelain / ceramic shell layer can form a tight bond with the cementitious material, thereby making the formed composite product have higher mechanical strength and more excellent lightweight, thermal insulation performance, etc. Therefore, the shell / core composite structure expanded perlite material of the present application can significantly improve the comprehensive performance of the lightweight, thermal insulation, fireproof and sound-absorbing material, thereby widening its application field and meeting the higher standard of building and widely developing application requirements.

[0035] Example 1

[0036] The present example provides a preparation method of a shell / core composite structure expanded perlite material.

[0037] Figure 1 The preparation process flow diagram of the shell / core composite structure expanded perlite is shown. The preparation method of the shell / core composite structure expanded perlite material of the present example will be described below. Figure 1

[0038] As Figure 1 ​As shown, the preparation method of the shell / core composite structure expanded perlite material mainly includes: crushing the perlite ore, checking and screening, and returning the particles with a particle size greater than +10 mesh to crushing; screening and classifying the particles with a particle size greater than +10 mesh, and the particles with a particle size less than +100 mesh can be used as other coating raw materials. The other coating raw materials can be crushed, mixed and ground to form three types of powder raw materials (inner coating powder, middle coating powder and outer coating powder), and the particle size of the three types of powder is -200 to -600 mesh. The particles with a particle size greater than +100 mesh obtained by screening and classifying are mixed with the sprayed binder to obtain first perlite particles. The inner coating powder, the middle coating powder and the outer coating powder are sequentially added to the first perlite particles for granulation to obtain second perlite particles. Specifically, the inner coating powder is added to the first perlite particles for stirring to obtain A-type second perlite particles, the middle coating powder is added to the A-type second perlite particles for stirring to obtain B-type second perlite particles, and the outer coating powder is added to the B-type second perlite particles for stirring to obtain C-type second perlite particles. The finally obtained second perlite particles are dried and preheated to obtain third perlite particles. The third perlite particles are subjected to high-temperature expansion treatment to obtain a shell / core composite shell expanded perlite (shell / core composite structure expanded perlite material).

[0039] Specifically, the preparation method of the shell / core composite structure expanded perlite material of the present example embodiment can include the following steps:

[0040] S1, the perlite ore particles are pretreated and mixed with a binder to obtain first perlite particles.

[0041] S2, glass coating powder, porcelain coating powder and ceramic coating powder are sequentially added to the first perlite particles for granulation to obtain second perlite particles.

[0042] S3, the second perlite particles are dried and preheated to obtain preheated third perlite particles.

[0043] S4, the third perlite particles are subjected to high-temperature expansion treatment to obtain a shell / core composite structure expanded perlite material.

[0044] In the present example embodiment, in step S1, the perlite ore particles can include one or more of perlite type, obsidian type, pitchstone type and pumice-like perlite. After pretreatment, perlite particles with a particle size range of +100 to -10 mesh (angular glass perlite particles) can be obtained.

[0045] In the present exemplary embodiment, in step S1, the pre-treatment processing can include: crushing, screening and dust removal; wherein the crushing is crushing with a screening section for checking, i.e., the oversize coarse perlite ore is continuously crushed to avoid over-crushing of the perlite ore (here, the crushing degree is 10 mesh, the oversize continues to participate in crushing, and the undersize enters the subsequent process). The screening and dust removal are to divide the crushed perlite ore into different particle size specifications by screening, and collect the fine powder with a particle size less than 100 mesh in the perlite ore after the screening, which can be used as a raw material for glassy coating powder and porcelain layer coating powder. Here, the fine powder with a particle size less than 100 mesh in the perlite ore is collected separately, which can include the fine powder collected under the -100 mesh screen and the dust collected by a bag dust removal method at the crushing and screening section.

[0046] Further, the division into different particle size specifications can include: -10 mesh to +20 mesh, -20 mesh to +25 mesh, -25 mesh to +50 mesh, -50 mesh to +80 mesh, and -80 mesh to +100 mesh.

[0047] In the present exemplary embodiment, in step S1, the ratio of the perlite particles (+100 to -10 mesh) obtained after the pre-treatment processing to the binder can be measured as a mass ratio of 100:(3-9) for different particle size specifications of the perlite particles and the binder, mixed uniformly to obtain first perlite particles. Here, the expanded perlite prepared by different particle size of the first perlite particles corresponds to different particle sizes, and the particle size of the first perlite (+100 mesh to -10 mesh) can also be selected according to the particle size of the coating powder (-200 mesh to -600 mesh). The use of different particle size particles and powder can obtain closed cell coating expanded perlite with better performance, and further have more excellent physical and chemical properties. Preferably, the perlite particle size is coarse, and the coating powder material can be fine or coarse; the perlite particle size is fine, and the coating powder material is as fine as possible.

[0048] Further, the uniform mixing can include: spraying the binder into the stirring perlite particles, and making the binder uniformly coated on the surface of the perlite particles, and the obtained first perlite particles are perlite particles coated with the binder on the surface. Spraying the binder into the stirring perlite particles can be achieved by atomizing the binder aqueous solution or hydrosol and spraying it into the stirring perlite particles by using a spraying device, wherein the spraying device includes one of a pressure spray head (spray), a sprayer and a compressed air spray gun.

[0049] In the present exemplary embodiment, in step S1, the binder used can include: an aqueous solution or hydrosol configured by industrial water and inorganic binder and / or organic binder.

[0050] The inorganic binder includes one or more of water glass, sodium silicate, and potassium silicate having a modulus of 1.0 to 2.9 (the modulus is used to modify the water glass, sodium silicate, and potassium silicate). When forming the binder, the inorganic binder can be configured as an aqueous solution having a density of 1.36 to 1.50 g / cm 3 having a Baumé degree of 38.4 to 48.3.

[0051] The organic binder includes one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, an acrylic acid emulsion, a vinyl acetate emulsion, a polyvinyl acetal glue, an emulsion glue, an animal glue, and a vegetable glue. When forming the binder, the organic binder can be configured as a hydrosol having a mass percentage of solid content of 0.5 to 2.0%.

[0052] When the binder is formed using a mixture of the inorganic binder and the organic binder, the volume ratio of the inorganic binder to the organic binder can be 5:1 to 2:1.

[0053] In the present exemplary embodiment, in step S2, the granulation is a process of coating the glassy shell powder, the porcelain shell powder, and the ceramic shell powder on the surface of the first perlite particles. The granulation can include: first mixing the glassy shell powder with the first perlite particles and bonding the glassy shell powder to the surface of the first perlite particles by the first perlite particle surface binder to form a glassy component coating layer, then sequentially adding one of the porcelain shell powder and the ceramic shell powder, completing the granulation, then adding the other of the porcelain shell powder and the ceramic shell powder, and continuing the granulation to form a porcelain and ceramic component coating layer. The specific granulation steps can include:

[0054] 1) Granulating the first perlite particles, the glassy shell powder, the porcelain shell powder, and the ceramic shell powder at a mass ratio of (90-75):(10-20):(1-15):(1-15).

[0055] 2) Placing the weighed first perlite particles in a granulator, and then uniformly adding the weighed glassy shell powder to the running granulator to uniformly coat the glassy shell powder on the first perlite particles.

[0056] The uniformly coating of the glassy shell powder on the first perlite particles means that the glassy shell powder does not exist independently after the coating is completed, but is entirely coated on the surface of the first perlite particles, has a dense texture, and tends to be spherical. A "composite particle of the glassy shell component / first perlite particle" is obtained.

[0057] 3) The weighed porcelain shell powder is first evenly added to the granulator running in step 2), so that the porcelain shell powder is evenly coated on the "glass shell component / first perlite particle composite particles" in step 2), and then the weighed ceramic shell powder is added to the running granulator for re-granulation. Or, the weighed ceramic shell powder is first evenly added to the granulator running in step 2), so that the ceramic shell powder is evenly coated on the "glass shell component / first perlite particle composite particles" in step 2), and then the weighed porcelain shell powder is added to the running granulator for re-granulation. In this way, the second perlite particle can be obtained after three times of granulation in step S2, and finally two kinds of shells can be formed, one of which includes a glass layer, a porcelain layer and a ceramic layer from inside to outside, and the other of which includes a glass layer, a ceramic layer and a porcelain layer from inside to outside. Although the order of adding the porcelain shell powder and the ceramic powder is different, the shell / core composite structure expanded perlite material of the application can be formed. The properties of the two kinds of shell / core composite structure expanded perlite materials with different shells are different, and when compared, the surface of the one with the porcelain layer as the outermost layer is denser and smoother, and has a lower water absorption rate; the surface of the one with the ceramic layer as the outermost layer has a higher strength, but a higher water absorption rate than the porcelain.

[0058] In step 3), the uniform coating of the porcelain and ceramic shell powders means that the porcelain and ceramic shell powders do not exist independently when the coating is completed, and form second perlite particles that are dense in texture and tend to be spherical. When the porcelain shell powder or the ceramic shell powder exists independently, an industrial water mist is sprayed on the corresponding granulated particles using a sprayer, and the coating process is continued until the shell powders are completely coated on the particles and the particles do not stick to each other.

[0059] In the example embodiment, in step S2, the glass shell powder can include the pre-processed perlite micro-powder with a particle size of less than 100 mesh, albite, borax and boric acid in a mass ratio of (50-70):(20-35):(2-10):(0-10). Further, the preparation method of the glass shell powder can include: the pre-processed perlite micro-powder with a particle size of less than 100 mesh, albite, borax and boric acid in a mass ratio of (50-70):(20-35):(2-10):(0-10) are mixed and ground to obtain the glass shell powder.

[0060] The porcelain sheath powder can be formed by mixing the pre-processed perlite powder with particle size less than 100 mesh, sodium / potassium feldspar, kaolin and quartz sand in a mass ratio of (10-30):(20-40):(20-30):(10-20). Further, the porcelain sheath powder can be prepared by mixing the pre-processed perlite powder with particle size less than 100 mesh, sodium / potassium feldspar, kaolin and quartz sand in a mass ratio of (10-30):(20-40):(20-30):(10-20) and then performing selective crushing and mixing and grinding.

[0061] The ceramic sheath powder can be formed by mixing the pre-processed perlite powder with particle size less than 100 mesh, sodium / potassium feldspar, kaolin and quartz sand in a mass ratio of (10-30):(20-40):(20-30):(10-20). Further, the porcelain sheath powder can be prepared by mixing the pre-processed perlite powder with particle size less than 100 mesh, sodium / potassium feldspar, kaolin and quartz sand in a mass ratio of (10-30):(20-40):(20-30):(10-20) and then performing selective crushing and mixing and grinding.

[0062] In the present exemplary embodiment, in step S2, the glass sheath powder has a particle size of -200 to -600 mesh, the porcelain sheath powder has a particle size of -200 to -600 mesh, and the ceramic sheath powder has a particle size of -200 to -600 mesh after the selective crushing, mixing and grinding.

[0063] In the present exemplary embodiment, in step S3, the drying can include a process of drying the second perlite particles in the drying-preheating device by increasing the temperature from room temperature to 200-300°C at a temperature increasing rate of 8-20°C / min in the drying section. The preheating can include a process of preheating the second perlite particles in the drying-preheating device by increasing the temperature from the drying section to 500-850°C at a temperature increasing rate of 50-80°C / min in the heating section.

[0064] In the present exemplary embodiment, in step S3, in the drying-preheating process, the air flow of the drying-preheating device is automatically directed from the heating section to the room temperature section. The third perlite particles after the drying and preheating processes have a water content of 2-3%.

[0065] In the present exemplary embodiment, the drying and preheating treatment in step S3 is a necessary step. The drying treatment is to reduce the water content on the surface of the second perlite particles, and the preheating treatment can reduce the water content inside the perlite particles. If the drying and preheating treatment is not performed, the water content on the surface and inside the perlite particles is too high, which can cause the perlite particles to absorb a large amount of heat during the evaporation of the excessive water, reduce the temperature difference of the perlite particles during the rapid heating, and prolong the expansion time of the perlite particles, so that the perlite particles cannot achieve the effect of instant expansion, and the expansion ratio of the perlite particles is affected. Meanwhile, the preheating can increase the temperature of the perlite particles before entering the expansion furnace, which is beneficial to the rapid reaching of the expansion temperature point of the perlite particles in the expansion furnace and the instant expansion of the perlite particles, and the expansion ratio of the perlite particles is improved.

[0066] In the present exemplary embodiment, in step S4, the high-temperature expansion treatment can include: uniformly scattering the third perlite particles after the drying and preheating treatment while hot onto a high-temperature flame in the expansion furnace, and the temperature of the high-temperature flame is maintained at 1100-1300°C, or uniformly spreading the third perlite particles after the preheating and directly sending them into the high-temperature section of the electric heating expansion furnace, and the temperature of the high-temperature section is maintained at 1150-1350°C, so that the third perlite particles are rapidly heated and quickly expanded. Here, the residence time (i.e., the time for quick expansion) of the third perlite particles in the high-temperature flame or the high-temperature section of the electric heating furnace is 2-80s, and the expanded perlite material with a shell / core composite structure is obtained.

[0067] In the present exemplary embodiment, during the high-temperature expansion treatment in step S4, the glassy coating powder material coated on the outer surface of the perlite ore particles is first melted, and the viscous glass melt formed is coated on the perlite particles. The viscous glass coating layer becomes a continuous coating layer as the perlite ore particles quickly expand, and can trap the gas released during the expansion of the first perlite particles, and the expansion ratio of the expanded perlite particles is significantly increased. The porcelain and ceramic coating components coated on the surface of the glassy coating powder material are sintered into a porcelain shell and a ceramic shell under high-temperature conditions, but do not melt. The non-melting sintered layer can better prevent the adhesion between the expanded perlite particles. As a result, not only a composite structure expanded perlite with a glassy, porcelain and ceramic shell layer is formed, but also a closed-cell expanded perlite is formed.

[0068] In the present exemplary embodiment, the present application is to make the perlite ore particles coated with a layer of glassy and porcelain and ceramic shell powder in advance, so that the perlite ore particles not only form a glassy inner layer and a porcelain outer shell and a ceramic outer shell during the expansion process, but also trap the gas released during the expansion process of the perlite ore particles, thereby achieving the purpose of reducing the bulk density, reducing the thermal conductivity, improving the sphericity and mechanical strength and other properties of the expanded perlite. The porcelain / ceramic heterogeneous material coated on the outer surface of the glassy heterogeneous material is fired to form a porcelain / ceramic shell, which has the effect of combining with the cement binder to form a high-strength composite material, thereby achieving the purpose of improving the performance of the expanded perlite and its composite material.

[0069] In the present exemplary embodiment, the obtained shell / core composite structure expanded perlite material is a closed-cell expanded perlite, and the combination of the glassy layer of the shell and the core and the porcelain layer and the ceramic layer of the shell is a gradient change combination relationship of mutual penetration of components during the expansion-fusion-sintering-firing process. The composite shell composed of glass, porcelain and ceramic is formed by the fusion of the glass shell component, the sintering of the porcelain shell component and the firing of the ceramic shell component. The composite shell has a combination of tight combination and component gradient change from the inside to the outside, i.e. glassy layer-glassy-porcelain layer-ceramic layer. The shell / core composite structure expanded perlite material has higher expansion ratio, higher mechanical strength, lower water absorption and slurry absorption, higher sound absorption rate and lower thermal conductivity than ordinary expanded perlite, and can be used to produce lightweight materials, thermal insulation materials, sound-absorbing and sound-insulating materials, fireproof and flame-retardant materials, etc., and can also be used instead of floating beads and lightweight or expanded ceramic particles.

[0070] Exemplary Embodiment 2

[0071] The present exemplary embodiment provides a shell / core composite structure expanded perlite material.

[0072] The shell / core composite structure expanded perlite material of the present exemplary embodiment can include a product prepared by the preparation method of the shell / core composite structure expanded perlite material described in the above exemplary embodiment 1.

[0073] Figure 2A A photograph of ordinary expanded perlite is shown; Figure 2B A photograph of shell / core composite structure expanded perlite is shown; Figure 3A An optical microscope photograph of ordinary expanded perlite is shown; Figure 3B An optical microscope photograph of shell / core composite structure expanded perlite is shown; Figure 4A An electron microscope photograph of ordinary expanded perlite is shown; Figure 4B An electron microscope photograph of shell / core composite structure expanded perlite is shown; Figure 5A An SEM image of a shell / core composite structure expanded perlite sample is shown;Figure 5B Another SEM image of the shell / core composite expanded perlite sample is shown below. Figures 2A to 5B To describe the shell / core composite structure expanded perlite material of this exemplary embodiment.

[0074] The shell / core composite expanded perlite material in this exemplary embodiment mainly comprises an outer shell and an inner shell. The outer shell, from the inside out, comprises a glassy layer, a ceramic layer, and a terracotta layer, or vice versa. The shell of this shell / core composite expanded perlite material is a composite shell composed of glassy, ​​ceramic, and terracotta materials; the inner shell is the expanded product of perlite-like mineral particles.

[0075] In this exemplary embodiment, the total thickness of the shell of the shell / core composite expanded perlite material can be 0.15 to 1 mm, wherein the thickness of the glassy layer, the ceramic layer and the ceramic layer can all be 0.05 to 0.5 mm; the diameter of the core is determined by the size of the perlite ore particles and the expansion ratio, and the diameter of the core can range from 2 to 28 mm.

[0076] In this exemplary embodiment, the shell / core composite expanded perlite material is closed-cell expanded perlite, and its properties may include:

[0077] The expansion ratio is as high as 3.5 to 8.0.

[0078] Lightweight: Bulk density of 200–350 kg / m³ 3 .

[0079] High mechanical strength: cylinder compressive strength is 0.8~2.3MPa.

[0080] It has good thermal insulation performance: the thermal conductivity coefficient is 0.040~0.075W / (m·K).

[0081] Water absorption rate is less than 0.5% to 1.5%.

[0082] Strong resistance to acids and alkalis: acid corrosion rate is less than 5%, and alkali corrosion rate is less than 1% (these are expressed as mass percentages).

[0083] like Figure 2A and Figure 2B As shown, conventional expanded perlite particles obtained by traditional methods have low sphericity, while the shell / core composite expanded perlite material of the present invention has high sphericity.

[0084] like Figure 3A and Figure 4A As shown, the surface of traditional expanded perlite contains pores and voids formed by the escape of gas during the expansion process, resulting in an uneven surface with sharp edges. Consequently, these pores easily absorb binders (such as cement paste, water glass, etc.).

[0085] As Figure 3B and Figure 4B shown, the shell / core composite structure of the expanded perlite of the present application has a vitreous inner layer and a porcelain outer layer of the expanded perlite shell, which encloses the pores of the expanded perlite. Therefore, it has excellent moisture-proof, waterproof, heat-insulating, sound-absorbing and sound-insulating properties. The surface layer of the material of the present application does not form a sintered layer with cracks during the high-temperature expansion process, which is beneficial to form a firm bond with the binder.

[0086] Obviously, compared with the conventional expanded perlite, the surface of the conventional expanded perlite is porous, and the binder usually enters the pores of the perlite, which greatly increases the amount of binder. The surface of the expanded perlite prepared by the method of the present application is dense, and the binder does not enter the perlite, so only a small amount of binder is needed to make the perlite particles adhere to each other.

[0087] From Figure 5A and Figure 5B , it can be seen that the expanded perlite prepared by the method of the present application has a multi-layer shell structure, so the method can successfully prepare expanded perlite with a shell / core composite structure.

[0088] In order to better understand the above-mentioned exemplary embodiments of the present application, the following further illustrates them with specific examples.

[0089] Example 1

[0090] (1) Crush, screen and dust the perlite ore to obtain perlite particles. Select perlite particles of -10 to +20 mesh. Select a water glass adhesive solution with a modulus of 2.0 and a density of 1.42 g / cm 3 , and a Baume degree of 43. According to the mass ratio of perlite particles to binder of 100:6, spray the binder on the surface of the perlite particles using a sprayer and mix uniformly to obtain the first perlite particles.

[0091] (2) The inner layer shell powder is prepared by mixing and grinding the micro-powder less than 100 mesh, potassium / sodium feldspar, borax and boric acid in a mass ratio of 51:34:6:9, and then crushing and mixing the mixture. The particle size of the inner layer shell powder is -500 mesh to +600 mesh. The middle layer shell powder is prepared by mixing and grinding the micro-powder less than 100 mesh, sodium / potassium feldspar, kaolin and quartz sand in a mass ratio of 20:40:30:10, and then crushing and mixing the mixture. The particle size of the middle layer shell powder is -500 mesh to +600 mesh. The outer layer shell powder is prepared by mixing and grinding the refractory clay, shale, potassium feldspar and quartz in a mass ratio of 34:27:24:15, and then crushing and mixing the mixture. The particle size of the outer layer shell powder is -400 mesh to -500 mesh.

[0092] First, the first perlite and the inner layer shell powder in an amount of 14% of the weight of the first perlite particles are added to a granulator, and then granulation is performed to obtain A-type second perlite particles. Then, the same amount of binder is added and mixed, and the middle layer shell powder in an amount of 5% of the weight of the first perlite particles is added and granulated (the same amount means that the A-type second perlite particles and the binder are mixed in a mass ratio of 100:6). Then, the same amount of binder is added and mixed, and the outer layer shell powder in an amount of 5% of the weight of the first perlite particles is added and granulated (the same amount means that the B-type second perlite particles and the binder are mixed in a mass ratio of 100:6). Finally, C-type second perlite particles are obtained.

[0093] (3) The C-type second perlite particles are placed in a drying device and dried at a temperature of 230°C with a temperature increasing rate of 19°C / min. Then, the C-type second perlite particles are placed in a high-temperature furnace preheated to 720°C, and preheated at 720°C for 8 min. Finally, third perlite particles with a water content of 2.3% are obtained.

[0094] (4) The preheated third perlite particles are evenly sprayed onto a high-temperature flame maintained at 1220°C in an expansion furnace, and high-temperature expansion treatment is performed for 23 s. The third perlite particles are rapidly heated and expanded to obtain a shell / core composite structure expanded perlite material (composite shell expanded perlite). The obtained composite shell expanded perlite has a shell / core composite structure, including a shell and an inner core. The thicknesses of the glass layer, the porcelain layer and the ceramic layer are 0.41 mm, 0.15 mm and 0.18 mm, respectively. The inner core is the expansion product of the first perlite, and the diameter of the inner core is determined by the particle size of the first perlite and the expansion multiple, and the diameter range is 24 mm.

[0095] The bulk density of the composite shell expanded perlite obtained by the example is 230 kg / m 3 ; the compressive strength is 1.2 MPa; the thermal conductivity coefficient is 0.046 W / (m·K); the water absorption is less than 1.34%; the acid etching amount is 3.37%; and the alkali etching amount is 0.86%.

[0096] Example 2

[0097] (1) The obsidian type ore is crushed, screened and dedusted to obtain perlite particles. The -30 mesh to +50 mesh perlite particles are selected, the binder is selected as a sodium silicate glue water solution with a modulus of 1.0 and a density of 1.36 g / cm 3 , the Baume degree of which is 38.4, and the binder is sprayed on the surface of the perlite particles and mixed uniformly according to a mass ratio of the perlite particles to the binder of 100:9, to obtain first perlite particles.

[0098] (2) The inner layer shell powder is selected from the less than 100 mesh micro powder produced by pretreatment, potassium / sodium feldspar, borax and boric acid in a mass percentage of 70:23:4:3, and is subjected to selective crushing and mixed powdering treatment to obtain the inner layer shell powder, the particle size of which is -400 mesh to +500 mesh. The middle layer shell powder is selected from the less than 100 mesh micro powder produced in the process of processing perlite type ore, sodium / potassium feldspar, kaolin and quartz sand in a mass percentage of 10:40:30:20, and is subjected to selective crushing and mixed powdering treatment to obtain the middle layer shell powder, the particle size of which is -400 mesh to +500 mesh. The outer layer shell powder is selected from refractory clay, shale, potassium feldspar and quartzite in a mass percentage of 46:32:17:5, and is subjected to selective crushing and mixed powdering treatment to obtain the outer layer shell powder, the particle size of which is -500 mesh to +600 mesh.

[0099] The first perlite and the inner layer shell powder in an amount of 18% of the weight of the first perlite particles are first added to a granulator, and then granulation is performed to obtain A-type second perlite particles. The same proportion of binder is added and mixed uniformly, and then the middle layer shell powder in an amount of 3% of the weight of the first perlite particles is added for granulation to obtain B-type second perlite particles. The same proportion of binder is added and mixed uniformly, and then the outer layer shell powder in an amount of 4% of the weight of the first perlite particles is added for granulation, and finally C-type second perlite particles are obtained.

[0100] (3) The C-type second perlite particles are placed in a drying device and dried at a temperature of 295℃ with a temperature rising rate of 13℃ / min, and then are placed in a high temperature furnace and preheated at a temperature of 850℃ for 8 min to obtain third perlite particles with a water content of 2.0%.

[0101] (4) The preheated third perlite particles are evenly sprayed onto the high-temperature flame in the expansion furnace with a temperature of 1150°C for high-temperature expansion treatment, and the expansion time is 8s, so that the third perlite particles are rapidly heated and quickly expanded to obtain composite shell expanded perlite. The obtained composite shell expanded perlite has a shell / core composite structure, including a shell and an inner core, wherein the thicknesses of the glassy layer, the porcelain layer and the ceramic layer are 0.46mm, 0.13mm and 0.17mm respectively; the inner core is the expansion product of the first perlite, and the diameter of the inner core is determined by the particle size and the expansion multiple of the first perlite, and the diameter range is 13mm.

[0102] The bulk density of the composite shell expanded perlite obtained in this example is 320kg / m 3 ; the compressive strength is 1.7MPa; the thermal conductivity coefficient is 0.062W / (m·K); the water absorption is less than 0.85%; the acid etching amount is 2.93%; and the alkali etching amount is 0.57%.

[0103] Example 3

[0104] (1) The pumice-like ore is crushed, screened and dedusted to obtain perlite particles, and perlite particles of-20 mesh to +30 mesh are selected. The binder is a potassium silicate glue solution with a modulus of 2.9 and a density of 1.5g / cm 3 , and the Baumé degree is 48.3. The mass ratio of the perlite particles to the binder is 100:4, the binder is sprayed on the surface of the perlite particles by a sprayer, and the mixture is uniformly mixed to obtain the first perlite particles.

[0105] (2) The inner layer of the shell powder is selected from the micro-powder less than 100 mesh produced by pre-treatment, potassium / sodium feldspar, borax and boric acid with a mass percentage of 59:25:8:8, and is treated by selective crushing and mixing and grinding to obtain the inner layer of the shell powder. The particle size of the inner layer of the shell powder is-325 mesh to +400 mesh. The middle layer of the shell powder is selected from the micro-powder less than 100 mesh produced in the process of processing perlite ore, sodium / potassium feldspar, kaolin and quartz sand with a mass percentage of 30:30:25:15, and is treated by selective crushing and mixing and grinding to obtain the middle layer of the shell powder. The particle size of the middle layer of the shell powder is-325 mesh to +400 mesh. The outer layer of the shell powder is selected from refractory clay, shale, potassium feldspar and quartzite with a mass percentage of 59:22:10:9, and is treated by selective crushing and mixing and grinding to obtain the outer layer of the shell powder. The particle size of the outer layer of the shell powder is-325 mesh to +400 mesh.

[0106] First perlite and inner layer shell powder in the proportion of 2% of the weight of the first perlite are added into the granulator, and then granulation is carried out to obtain A-type second perlite particles. Then, the same proportion of binder is added and mixed uniformly, and then 10% of the weight of the first perlite is added to the middle layer shell powder for granulation to obtain B-type second perlite particles. Then, the same proportion of binder is added and mixed uniformly, and then 8% of the weight of the first perlite is added to the outer layer shell powder for granulation to obtain C-type second perlite particles.

[0107] (3) The C-type second perlite particles are placed in a drying device and dried at a temperature of 205℃ with a temperature rising rate of 8℃ / min, and then they are placed in a high-temperature furnace and preheated at a temperature of 510℃ for 8min to obtain third perlite particles with a water content of 2.9%.

[0108] (4) The preheated third perlite particles are evenly sprinkled onto a high-temperature flame in an expansion furnace with a temperature of 1290℃ for high-temperature expansion treatment, and the expansion time is 35s, so that the third perlite particles are rapidly heated and quickly expanded to obtain composite shell expanded perlite. The obtained composite shell expanded perlite has a shell / core composite structure, including a shell and an inner core, wherein the thicknesses of the glassy layer, the porcelain layer and the ceramic layer are 0.07mm, 0.33mm and 0.27mm respectively; the inner core is the expansion product of the first perlite, and the diameter of the inner core is determined by the particle size of the first perlite and the expansion multiple, and the diameter range is 2mm.

[0109] The bulk density of the composite shell expanded perlite obtained in this example is 350kg / m 3 ; the compressive strength is 2.3MPa; the thermal conductivity coefficient is 0.075W / (m·K); the water absorption is less than 0.53%; the acid etching amount is 3.29%; and the alkali etching amount is 0.35%.

[0110] The following Tables 1-4 show the specific test parameters used in Examples 4-7 and the properties of the composite shell expanded perlite obtained.

[0111] Table 1 Particle size of perlite, type and parameters of binder

[0112]

[0113]

[0114] Table 2 Formulation of glassy shell, porcelain shell and ceramic shell

[0115]

[0116] Table 3 Parameters of drying, preheating and heating expansion processes

[0117]

[0118] Table 4 Properties of composite shell expanded perlite

[0119]

[0120] In summary, the advantages of the present application include at least one of the following:

[0121] (1) The glassy shell powder of the inner layer of the shell has a lower melting temperature than the expansion temperature of the perlite ore particles, i.e. the glassy shell powder is melted before the perlite ore particles expand during the calcination process (high-temperature expansion stage), thereby effectively trapping the gas generated during the expansion of the perlite ore particles and increasing the expansion ratio of the expanded perlite, and forming a closed-cell expanded perlite material after cooling.

[0122] (2) The ceramic or porcelain shell powder of the outer layer of the shell / core composite structure expanded perlite shell is sintered or fired into a ceramic or porcelain body during the expansion of the perlite ore particles during calcination, and forms a ceramic or porcelain material coating layer on the outer surface of the expanded perlite. The ceramic or porcelain shell coating layer has a higher bonding strength with the organic binder and inorganic cementitious material during the preparation of the expanded perlite composite material, which is of great significance for the preparation of high-strength expanded perlite composite materials.

[0123] (3) The shell / core composite structure expanded perlite not only has closed pores on the surface, i.e. closed-cell expanded perlite, but also has a higher degree of sphericity, making it easier to form a more compact packing body. These characteristics can greatly reduce the amount of organic binder or inorganic cementitious material required during the preparation of the expanded perlite composite material, thereby not only reducing production costs, but also significantly improving the thermal insulation, sound absorption and sound insulation performance of the expanded perlite composite material after reducing the amount of organic binder or inorganic cementitious material (such as cement).

[0124] (4) The preparation and unique design of the shell / core composite structure of the expanded perlite effectively seals the internal pores, effectively reducing the absorption of moisture and humidity by the expanded perlite material, thereby ensuring the lightweight performance and excellent thermal insulation and sound absorption and sound insulation performance of the material. Therefore, the composite materials or products prepared using the shell / core composite structure expanded perlite have superior process technology performance, and have a particularly broad application prospect in the contemporary society that pursues high efficiency, energy saving and environmental protection.

[0125] Although the present application has been described above by incorporating example embodiments, it should be apparent that various modifications and changes can be made without departing from the spirit and scope of the application as defined in the appended claims.

Claims

1. A shell / core composite expanded perlite material, characterized in that, The shell / core composite expanded perlite material includes an outer shell and an inner core. The outer shell consists of a glassy layer, a ceramic layer, and a ceramic layer from the inside out, or the outer shell consists of a glassy layer, a ceramic layer, and a porcelain layer from the inside out. The inner core is an expanded product of perlite ore particles.

2. The shell / core composite expanded perlite material according to claim 1, characterized in that, The total thickness of the outer shell is 0.15–1 mm, wherein the thickness of the glass layer, ceramic layer, and earthenware layer is 0.05–0.5 mm; the diameter of the core ranges from 2 to 28 mm.

3. A method for preparing the shell / core composite expanded perlite material as described in claim 1, characterized in that, The preparation method includes: Perlite ore particles are pre-treated and then mixed with a binder to obtain the first perlite particles. First, add glassy coating powder to the first perlite particles for granulation, then add ceramic coating powder for granulation, and finally add ceramsite coating powder for granulation; or, first add glassy coating powder to the first perlite particles for granulation, then add ceramsite coating powder for granulation, and finally add ceramic coating powder for granulation; to obtain the second perlite particles. The second perlite particles are dried and preheated to obtain the third perlite particles; The third type of perlite particles were subjected to high-temperature expansion treatment to obtain a shell / core composite structure expanded perlite material.

4. The method for preparing the shell / core composite expanded perlite material according to claim 3, characterized in that, The perlite ore particles include one or more of the following: perlite type, obsidian type, resinstone type, and pumice-like perlite.

5. The method for preparing the shell / core composite expanded perlite material according to claim 3, characterized in that, The pre-treated perlite particles with a particle size range of +100 to -10 mesh are mixed with the binder at a mass ratio of 100:(3 to 9) to obtain the first perlite particles.

6. The method for preparing the shell / core composite expanded perlite material according to claim 3, characterized in that, The adhesive comprises an aqueous solution or hydrosol prepared with industrial water and inorganic and / or organic adhesives; wherein... The inorganic binder comprises one or more of water glass, sodium silicate, and potassium silicate with a modulus of 1.0 to 2.9, and is formulated to have a density of 1.36 to 1.50 g / cm³. 3 The aqueous solution has a Baumé degree of 38.4–48.3; The organic binder includes one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, acrylic emulsion, vinyl acetate emulsion, polyvinyl alcohol acetal, emulsion glue, animal glue, and plant glue, and is formulated into a water-soluble adhesive with a solid content of 0.5% to 2.0% by mass using the organic binder. When the inorganic binder and the organic binder are mixed to form the binder, the volume ratio of the inorganic binder to the organic binder is 5:1 to 2:

1.

7. The method for preparing the shell / core composite expanded perlite material according to claim 3, characterized in that, The first perlite particles, the glassy coated powder, the porcelain coated powder, and the ceramic coated powder are granulated at a mass ratio of (90-75):(10-20):(1-15):(1-15).

8. The method for preparing the shell / core composite expanded perlite material according to claim 3, characterized in that, The glassy coating powder is formed by mixing perlite powder with a particle size of less than 100 mesh obtained after pretreatment in the mass percentage ratio of (50-70):(20-35):(2-10):(0-10), albite, borax and boric acid; the particle size of the glassy coating powder is -200 to -600 mesh. The ceramic-coated powder is formed by mixing perlite powder with a particle size of less than 100 mesh obtained after pretreatment in the following mass percentage ratios: (10-30):(20-40):(20-30):(10-20); sodium / potassium feldspar, kaolin, and quartz sand; the particle size of the ceramic-coated powder is -200 to -600 mesh. The ceramic coating powder is formed by mixing refractory clay, shale, potassium feldspar and quartzite in a mass percentage ratio of (30-60):(20-40):(10-25):(5-15); the particle size of the ceramic coating powder is -200 to -600 mesh.

9. The method for preparing the shell / core composite expanded perlite material according to claim 3, characterized in that, The drying process includes drying the second perlite particles by heating them from room temperature to 200-300°C at a heating rate of 8°C-20°C / min. The preheating includes preheating the second perlite particles at a temperature of 500–850°C; The third perlite grains have a water content of 2-3%.

10. The method for preparing the shell / core composite expanded perlite material according to claim 3, characterized in that, The high-temperature expansion treatment includes: allowing the third perlite particles to be held in a high-temperature environment of 1100-1350℃ for 2-80 seconds to be rapidly heated and expand.